Second chance in Sri Lanka - Milne, Nina (Harlequin romance, 2022)
When sparks fly again... miracles can happen! Seeing her ex-husband, Matt, again was meant to bring Zoe closure, not butterflies! But with memories of their marriage, which ended in heartbreak, impossible to ignore, her sister's Sri Lankan island wedding is a welcome distraction. Until Zoe and Matt are gifted a break alone on the beautiful island! It's an opportunity to prove they were never compatible and finally move on. Or, secluded in paradise, will they discover they were always meant to be?